2010
DOI: 10.1152/ajpheart.00617.2009
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression and secretion of resistin in epicardial adipose tissue of patients with acute coronary syndrome

Abstract: The purpose of this study was to test the hypothesis that specific epicardial adipose tissue (EAT) proinflammatory adipokines might be implicated in acute coronary syndrome (ACS). We compared expression and protein secretion of several EAT adipokines of male ACS with those of matched stable coronary artery disease (CAD) patients and controls with angiographically normal coronary arteries. The effect of supernatant of cultured EAT on endothelial cell permeability in vitro was also evaluated in the three study g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 31 publications
1
58
1
4
Order By: Relevance
“…However, other studies have reported IL8 increases in EAT (70,88), perhaps due to population differences. Previous studies have reported that SERPINE1 was found to be increased in EAT from patients with severe stable CAD (70) and overexpressed in EAT from acute coronary syndrome (43). In our study, SERPINE1 gene expression correlates with the lipolysis results, indicating that increased lipolysis associates with increased inflammation observed in SAT, whereas the decreased lipolysis and inflammatory gene expression observed in EAT may indicate a possible protective mechanism toward the cardiomyocyte.…”
Section: E560 Eat Metabolism In Heart Failure Patientssupporting
confidence: 67%
See 1 more Smart Citation
“…However, other studies have reported IL8 increases in EAT (70,88), perhaps due to population differences. Previous studies have reported that SERPINE1 was found to be increased in EAT from patients with severe stable CAD (70) and overexpressed in EAT from acute coronary syndrome (43). In our study, SERPINE1 gene expression correlates with the lipolysis results, indicating that increased lipolysis associates with increased inflammation observed in SAT, whereas the decreased lipolysis and inflammatory gene expression observed in EAT may indicate a possible protective mechanism toward the cardiomyocyte.…”
Section: E560 Eat Metabolism In Heart Failure Patientssupporting
confidence: 67%
“…In our study, SERPINE1 gene expression correlates with the lipolysis results, indicating that increased lipolysis associates with increased inflammation observed in SAT, whereas the decreased lipolysis and inflammatory gene expression observed in EAT may indicate a possible protective mechanism toward the cardiomyocyte. Moreover, depending on the models studied, SERPINE1 may be regulated by insulin and by prescribed medications (25,43,53,76). However, we did not detect any effect of diabetes on inflammatory markers when comparing with nondiabetics with HF.…”
Section: E560 Eat Metabolism In Heart Failure Patientscontrasting
confidence: 54%
“…Epicardial adipose tissue is a true visceral fat tissue that deposits not only on the free wall of right ventricle and on the left ventricular apex, but also around the atria [16,17] . The epicardial adipose tissue is significantly associated with the development of heart diseases [18][19][20] .…”
Section: Discussionmentioning
confidence: 99%
“…Среди изученных посредников развития и прогрес-сирования эндотелиальной дисфункции необходи-мо отметить резистин, изучение которого в послед-нее время проводится не только в группе больных с метаболическим синдромом и сахарным диабетом, но и в когорте пациентов с ОКС. В 2010 году, на-учно-исследовательской группой показано, что при наличии острой ишемии миокарда концентрация плазменного резистина повышается, а вместе с тем увеличивается и проницаемость сосудов [13], что является одним из главных механизмов перераспре-деления водных секторов организма. Аналогичные данные были получены и при проведении других исследований по установлению зависимости кон-центрации резистина плазмы и прогрессирования атеросклероза [11].…”
Section: Discussionunclassified